Centro de investigación y capacitación en gestión de residuos en la ciudad de Quibdó Chocó (2021)
Architectural practices are responsible for generating waste, as well as its construction, use and demolition worldwide, and buildings account for 56% of the pollution in our cities. The consequences on climate change and our ecosystem are consequent on the use and manufacture of materials from natural resources that are not renewable. In Colombia, the construction industry consumes 60% of the materials extracted from the earth and 40% of waste (Ministry of the Environment and Sustainable Development). Quibdó is one of the most polluted cities in the country by waste and the potential in natural resources is wasted, despite being one of the places with the greatest ecological wealth and diversity, the city is losing its ecosystem.